2017
DOI: 10.1186/s13073-017-0400-x
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional assessment of B-cell responses to quadrivalent meningococcal conjugate and plain polysaccharide vaccine

Abstract: Background Neisseria meningitidis is a globally important cause of meningitis and septicaemia. Twelve capsular groups of meningococci are known, and quadrivalent vaccines against four of these (A, C, W and Y) are available as plain-polysaccharide and protein-polysaccharide conjugate vaccines. Here we apply contemporary methods to describe B-cell responses to meningococcal polysaccharide and conjugate vaccines.MethodsTwenty adults were randomly assigned to receive either a meningococcal plain-polysaccharide or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
(59 reference statements)
6
11
0
Order By: Relevance
“…Consistent with previous reports, we observed the upregulation of genes associated with terminally differentiated, antibody‐secreting B cells (plasma cells) at 7 days post‐vaccination (Obermoser et al , 2013; O'Connor et al , 2017). Of note, we identified a particular gene encoding an immunoglobulin light chain molecule, IGLV9‐49, that was upregulated after vaccination with 4CMenB vaccine compared with control vaccines alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous reports, we observed the upregulation of genes associated with terminally differentiated, antibody‐secreting B cells (plasma cells) at 7 days post‐vaccination (Obermoser et al , 2013; O'Connor et al , 2017). Of note, we identified a particular gene encoding an immunoglobulin light chain molecule, IGLV9‐49, that was upregulated after vaccination with 4CMenB vaccine compared with control vaccines alone.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we defined baseline whole blood gene signatures that were predictive of vaccine immunogenicity and reactogenicity. There are an increasing number of studies describing transcriptional responses to immunisation in adults (Obermoser et al, 2013;Nakaya et al, 2015;O'Connor et al, 2017). However, there are few data describing transcriptional regulation following infant immunisation-despite most vaccination programmes being targeted to this population (ECDC, 2020; WHO, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In our pre-specified analysis plan, gene expression correlations were restricted to the clusters discovered by GSEA and not the data-driven clusters identified and display in the UMAPs ( Fig 2B–2D ), in order to limit the number of comparisons and thereby reduce the likelihood of false discoveries. However, because other groups have identified plasmablast signatures that are associated with subsequent antibody titers after meningococcal [ 45 ], yellow fever [ 46 ], malaria [ 47 ], and influenza [ 48 ] vaccination, we note here that the genes we identified in cluster IV represent a plasmablast signature ( S3 Table ). Consistent with these other studies, a further exploratory analysis indicates that the increase in expression of genes in cluster IV on Day 7 was positively correlated with 92TH023 gp120 (AE) specific IgG measured at Month 6.5 (rho = 0.48, p = 0.02) and Month 12 (rho = 0.66, p = 0.0009).…”
Section: Discussionmentioning
confidence: 82%
“…However, the mechanism by which the response to serotype W is reduced in the pure polysaccharide vaccine is unclear, although it is suggested that there may be some sort of negative feedback mechanism present when polysaccharide vaccines are used. This may be explained by O'Connor et al (2017), who found that as well as being less effective at eliciting a response, polysaccharide vaccines might take a role in actively depleting B memory cells when used as a booster vaccine, a mechanism that may also explain the findings of Rothstein et al (1991). Borja-Tabora et al (2015) and Holme et al (2015) studied a meningococcal vaccine (Men) with the serotypes A, C, W and Y polysaccharides either linked to TT as a glycoconjugate or as a polysaccharide-only vaccine.…”
Section: Comparison Of Glycoconjugate and Polysaccharide Vaccinesmentioning
confidence: 99%